2014
DOI: 10.4046/trd.2014.77.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Inhibits Expression and Activity of Matrix Metalloproteinase in Human Lung Fibroblasts (HFL-1) Cells

Abstract: BackgroundLow levels of serum vitamin D is associated with several lung diseases. The production and activation of matrix metalloproteinases (MMPs) may play an important role in the pathogenesis of emphysema. The aim of the current study therefore is to investigate if vitamin D modulates the expression and activation of MMP-2 and MMP-9 in human lung fibroblasts (HFL-1) cells.MethodsHFL-1 cells were cast into three-dimensional collagen gels and stimulated with or without interleukin-1β (IL-1β) in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
2
22
0
2
Order By: Relevance
“…However, although increased expression of MMP-2 and -9 was observed, the cellular signalling mechanism driving this phenotype was also not explored, again demonstrating the limited knowledge in this area. Particularly, considering that other studies in human lung fibroblasts and uterine fibroid cells showed that VitD metabolites actually inhibited MMP-2 and -9 expression by modulating cytokine expression (Halder et al 2013, Kim et al 2014, which are key regulators of immune cell infiltration. Nonetheless, these conflicting effects may be explained by the complex mechanism of VDR and VDRE regulation as outlined earlier.…”
Section: R36mentioning
confidence: 99%
“…However, although increased expression of MMP-2 and -9 was observed, the cellular signalling mechanism driving this phenotype was also not explored, again demonstrating the limited knowledge in this area. Particularly, considering that other studies in human lung fibroblasts and uterine fibroid cells showed that VitD metabolites actually inhibited MMP-2 and -9 expression by modulating cytokine expression (Halder et al 2013, Kim et al 2014, which are key regulators of immune cell infiltration. Nonetheless, these conflicting effects may be explained by the complex mechanism of VDR and VDRE regulation as outlined earlier.…”
Section: R36mentioning
confidence: 99%
“…46,[73][74][75][76] In addition to polyadenylation signals, so-called "terminators", such as the human gastrin terminator, have been described to play an important role in transcription terminator. 77 In our AS construct, neither addition of polyadenylation signals or gastrin terminator in the intron, nor addition of the gastrin terminator at the end of the expression cassette had an effect on secretion or cell surface display.…”
Section: Discussionmentioning
confidence: 75%
“…The gastrin terminator was described to detach the transcription machinery from the DNA. 77 Added at the end of the expression cassette after the polyadenylation signal, it may affect splicing, but the addition of the gastrin terminator at the end of the expression cassette had no significant impact on either surface staining or titer (data not shown).…”
Section: Modulation Of Splice Ratio and Signal By Modification Of Intmentioning
confidence: 96%
“…48,49 Moreover, it can inhibit chemokine and cytokine expression, monocyte accumulation, and inducible nitric oxide synthaseaccumulation in the CNS. 50,51 It can also suppress the expression and activity of Matrix metalloproteinases-2 and-9 (MMP-2 and MMP-9), 52 which are associated with a risk of MS. 53 Although many investigators have demonstrated the effect of vitamin D supplementation on MS or experimental autoimmune encephalomyelitis (EAE) models, the exact modulation pathways remain elusive. Several theories have been proposed to explain the modulation effects of vitamin D on MS pathophysiology: (1) Vitamin D supplementation could increase the vitamin D receptor (VDR)-binding sites across the genome, 25 which were found to be enriched in genes previously associated Figure 1.…”
Section: Journal Of Central Nervous System Diseasementioning
confidence: 99%